1963
DOI: 10.1530/jrf.0.0050123
|View full text |Cite
|
Sign up to set email alerts
|

Sex Steroid Hormones and Voluntary Exercise in Rats. A Correction

Abstract: A result reported earlier that oestradiol sensitizes the nervous system of the male rat so that it responds to testosterone with increased motor activity could not be repeated. The male and female rat respond differently, the male only to oestradiol and the female to both oestradiol and testosterone. A few rats sometimes respond to testosterone.Oestradiol benzoate pellets implanted beneath the skin of the gonadectomized rat cause both males and females to take large amounts of exercise in an activity drum. Tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1972
1972
1976
1976

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…Stern and Murphy (1971) demonstrated that an antiandrogen, cyproterone acetate, would not antagonize the effects of TP on running. The suggestion that estradiol is more effective than testosterone was substantiated and quantified (Asdell & Sperling, 1963). The dose of TP we used was 100 times the dose of EB, yet EB still induced higher levels of activity.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Stern and Murphy (1971) demonstrated that an antiandrogen, cyproterone acetate, would not antagonize the effects of TP on running. The suggestion that estradiol is more effective than testosterone was substantiated and quantified (Asdell & Sperling, 1963). The dose of TP we used was 100 times the dose of EB, yet EB still induced higher levels of activity.…”
Section: Discussionmentioning
confidence: 93%
“…Wide variations among individual responses to hormonal treatments are not uncommon on activity measures, especially with testosterone treatments. Asdell and Sperling (1963) found definite responders and nonresponders to TP pellets at doses from 1 mg to 20 mg (using only two animals per group). Hoskins (1925) reported that some male rats did not show a decrease in running activity after castration until 24 days postoperatively, whereas the activity of some males declined immediately.…”
Section: Discussionmentioning
confidence: 94%
“…All animals were gonadectomized at 4 wk of age. Prepubertal castration was used to avoid the possible sensitization of the activity response by preexposure to estradiol (Asdell, Doornenbal, & Sperling, 1962;Asdell & Sperling, 1963).…”
Section: Experiments 2: Running-wheel Activity Methodsmentioning
confidence: 99%
“…The administration of estrogen [3] or the sc placement of estrone pellets [I0] increase activity in ov-x rats. Subcutaneous implants of estrogen stimulate running activity in castrate male rats [1]. Lastly, progesterone on a background of estrogenic stimulation does not result in more activity than estrogen alone [4,9].…”
Section: Estradiol Benzoate Treatment (Days 57-70)mentioning
confidence: 99%